Numerical assessment of the potential of fibre reinforced shotcrete for structural strengthening of underground masonry tunnels - Taheri, Mahsa (2022)
Strengthening and rehabilitation of underground tunnels are frequently an inseparable part of upgrading the railway network. Short fibres have been replacing pre-installed steel mesh with technical and economic ad vantages on the stabilization and securing of rock and soil systems in underground tunnels through the fibre reinforced shotcrete (FRS) technology. The strengthening efficiency of this technology can be even increased by shotcreting suitable arrangements of strain-softening and strain-hardening fibre reinforced concrete (SSFRC and SHFRC), despite requiring technological developments in terms of mix compositions and shotcrete equipment. The potential of combining SSFRC and SHFRC for the strengthening of underground tunnels is explored in this paper through numerical simulations based on the finite element method. The predictive performance of the adopted material nonlinear constitutive models is initially validated by simulating experimental tests where SSFRC and SHFRC were used for the strengthening of masonry elements or for the prefabrication of tunnel segments. By using a layered curved shell model, the potential of various strengthening configurations is assessed for a typical Portuguese underground tunnel by demonstrating the gains in terms of stiffness and load carrying capacity when proper use of SSFRC and SHFRC is adopted. It is revealed that, by using a shotcrete technology capable of placing SSFRC and SHFRC in layers according to the outputs of advanced numerical analysis, an efficient strengthening system with a significant reduction of consumed materials can be achieved.